Total Synthesis of Blennolide Mycotoxins: Design, Synthetic Routes and Completion1. Issue 22 (1st July 2014) - Meister, Anne C.; Encinas, Arantxa; Sahin, Hülya; Singer, Emilie M. C.; Nising, Carl F.; Nieger, Martin; Bräse, Stefan
Abstract: Mycotoxins of the tetrahydroxanthone class of natural products possess a large number of interesting biological properties. In this full paper, we present our synthetic strategy to some members of this class of compounds, namely the blennolides A and C. We disclose the scope and limitations of the functionalization of various xanthones derived from a domino oxa‐Michael‐aldol condensation and pursue dimerization of these xanthones. Furthermore, the first crystal structure of blennolide C has been obtained. Abstract : Two total syntheses of monomeric tetrahydroxanthone natural products are presented. The introduction of various functional groups by nucleophilic addition is extensively examined, and efforts towards the dimerization of these xanthones are reported.